2005
DOI: 10.1063/1.2117626
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis of nanoscale double-stranded DNA and humidity effects on its electrical conductivity

Abstract: Differential conductance as a promising approach for rapid DNA sequencing with nanopore-embedded electrodes Appl. Phys. Lett. 97, 043701 (2010); 10.1063/1.3467194Electrical detection of single-base DNA mutation using functionalized nanoparticles Appl. Phys. Lett. 95, 073703 (2009); The dielectrophoresis method for trapping and attaching nanoscale double-stranded DNA between nanoelectrodes was developed. The method gives a high yield of trapping single or a few molecules only which enables transport measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 51 publications
5
88
1
Order By: Relevance
“…The result is a smaller self-energy and a larger resulting conductivity. Surprisingly, experiments on individual DNA molecules [9], DNA films [10,11,12,13], and DNA bundles [7,8] all show a similar exponential dependence of conductivity on humidity. The lack of a geometry-dependent difference remains a puzzle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is a smaller self-energy and a larger resulting conductivity. Surprisingly, experiments on individual DNA molecules [9], DNA films [10,11,12,13], and DNA bundles [7,8] all show a similar exponential dependence of conductivity on humidity. The lack of a geometry-dependent difference remains a puzzle.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies examining the electrical properties of double-helical DNA and DNA bundles have found a similar dependence of conductivity on relative humidity [7,8,9]. Experimental data shows that the conductivity of DNA increases by a simple exponential over nearly the entire range of relative humidity (10% to 100%), and spans roughly six orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The dielectrophoretic force has been used to make contact less tweezers for single cell manipulation. 8 Furthermore, it has been used to control biomolecules, 9 DNA, 10,11 nanowires, 12 bundles of carbon nanotubes, 13 and single-walled carbon nanotubes. 14 Polarization forces are also used in electrohydrodynamic continuous flow micropumps 15,16 and to operate dropletbased lab-on-a-chip.…”
Section: Introductionmentioning
confidence: 99%
“…The actual magnitude of DNA conductivity and its physical mechanism is still under debate, since experiments indicate that the discussed biomolecule can behave as: an Anderson insulator [7][8][9][10][11], a wide-band-gap semiconductor [12][13][14][15][16], an Ohmic conductor [17][18][19][20][21][22][23][24] or even a proximity-induced superconductor [25]. Among all of the conditions that can have a significant influence on the experimental results, we can enumerate: DNA base sequence, molecular length, orientation in space, stretching, nature of the molecule-electrode contact, ambient surrounding (humidity), temperature of the system, adsorption surface, structural form of the molecule (bundle or single chain), and preparation conditions.…”
mentioning
confidence: 99%